1990
DOI: 10.1111/j.1751-1097.1990.tb01972.x
|View full text |Cite
|
Sign up to set email alerts
|

Hemoprotein(s) Mediate Blue Light Damage in the Retinal Pigment Epithelium*

Abstract: In order to elucidate the mechanisms of blue light damage on ocular tissues, the transepithelial transport, electrical characteristics and ultrastructural properties of irradiated isolated bovine retinal pigment epithelium (RPE) were investigated. Blue light (430 nm) irradiation at 20 mW/cm2 significantly reduced the transepithelial potential and short circuit current of RPE. During blue light exposure, a decrease in chloride transport was observed, and this decrease appeared to be closely coupled to changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 23 publications
1
28
0
Order By: Relevance
“…Crockett and Lawwill showed that damage to cultured RPE from blue light (435 nm) is directly proportional to the oxygen concentration within the culture medium (44). Pautler et al (47) demonstrated that blue light exposure to isolated RPE affects the molecular transport capabilities of the RPE and lowers their capacity for oxygen uptake. The use of antioxidants, including dimethylthiourea (50), the spin-trapping reagent phenyl-Ntert-butylnitrone (51), and, more importantly, ascorbic acid, which is naturally found in abundance in the retina but decreases during intense light exposure (52), appears to help alleviate light damage within the retina and RPE (53)(54)(55)(56).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Crockett and Lawwill showed that damage to cultured RPE from blue light (435 nm) is directly proportional to the oxygen concentration within the culture medium (44). Pautler et al (47) demonstrated that blue light exposure to isolated RPE affects the molecular transport capabilities of the RPE and lowers their capacity for oxygen uptake. The use of antioxidants, including dimethylthiourea (50), the spin-trapping reagent phenyl-Ntert-butylnitrone (51), and, more importantly, ascorbic acid, which is naturally found in abundance in the retina but decreases during intense light exposure (52), appears to help alleviate light damage within the retina and RPE (53)(54)(55)(56).…”
mentioning
confidence: 99%
“…Studies have shown that intense and long duration exposure to excessive light can induce damage to both the retina and RPE (43)(44)(45)(46)(47), with the greatest susceptibility to injury arising from wavelengths of light near the maximum absorption region of rhodopsin (ϳ500 nm) and in the blue/UV-A region (320 -450 nm) (45,46). Evidence suggests that green light exposure is most responsible for damage incurred through chronic low level exposure, while blue/UV-A light-induced damage is incurred through short intense exposures (i.e.…”
mentioning
confidence: 99%
“…An ensuing redistribution of chlorine is detected, followed by the swelling and deformation of the mitochondria in the IS, ultimately leading to the destruction of photoreceptors [5]. The inactivation of the CYO by blue light is also exhibited in studies in vitro [26,27,43,44]. Consequently, the irreversible inhibition of critical enzyme(s) involved in cellular metabolism is a likely factor in blue light-mediated damage.…”
Section: Discussionmentioning
confidence: 99%
“…Other potentially harmful retinal photosensitisers include cytochrome oxidase and rhodopsin with its photoproducts. 37,39,[83][84][85][86] Most of these retinal photosensitisers, except for rhodopsin, are maximally excited in the violet-blue part of the spectrum: porphyrins peak at 400 nm and cytochrome oxidase at 420 to 440 nm. 39,87 Lipofuscin accumulates in the RPE with age and is also found in a number of retinal disorders.…”
Section: Blue Light and Amdmentioning
confidence: 99%